Peran Kepala Desa Dalam Pengelolaan Badan Usaha Milik Desa Di Desa Masago Kecamatan Patimpeng Kabupaten Bone - Noviana, Noviana; Mone, Ansyari; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2022)
This study purposed to determine the role of the village head in the management of Masago village-owned enterprises and also the supporting and inhibit factore for the role of the village head in managing BUMDes. This study used qualitative research. Sources of data used primary data and secondary data. The data collection methods used observation, interview and dokumentation methods. The technique of analysing data through three stages, namely the stage of data education, data display and data verification. The results of the study showed that the role of the village head in managing BUMDesa Mangngiri was seen from three indicators, namely interpersonal roles, roles related to information and decision making roles. In this case, the village head played a sufficient role in the establishment and planning of business units, but it was the village head was still not maximal in monitoring and advising the performance of BUMDesa, the village head of Masago had not fully played a role in managing Bumdes Mangngiri. Keywords: Role, Village Head, Management, village-owned enterprises